Does aid work ? : report to an intergovermental task force - "Cassen , Robert" (Oxford, 1986)
The question of the effectiveness or counter-productivity of foreign aid is one of the great issues facing the world today. This volume arose from a study conducted for an inter-governmental task force. The team surveyed the published literature, reviewed existing evaluations of aid projects, and undertook seven detailed country studies. The basic finding is that the majority of aid succeeds in terms of its own objectives and obtains a reasonable rate of return. At the same time, this book analyses the frequent failings of aid projects, compares these failings with other forms of private and public investment, and proposes measures for improving aid effectiveness.
Keywords: Aid